CSF-1 receptor-mediated differentiation of a new type of monocytic cell with B cell-stimulating activity: its selective dependence on IL-34. Issue 1 (19th September 2013) - Yamane, Fumihiro; Nishikawa, Yumiko; Matsui, Kazue; Asakura, Miki; Iwasaki, Eriko; Watanabe, Koji; Tanimoto, Hikaru; Sano, Hiroki; Fujiwara, Yuki; Stanley, E Richard; Kanayama, Naoki; Mabbott, Neil A; et al.
Abstract : Occurrence of a CSF-1 receptor-dependent monocyte differentiation process driven by IL-34, but not CSF-1. ABSTRACT: With the use of a mouse FDC line, FL-Y, we have been analyzing roles for FDCs in controlling B cell fate in GCs. Beside these regulatory functions, we fortuitously found that FL-Y cells induced a new type of CD11b + monocytic cells (F4/80 +, Gr-1 −, Ly6C −, I-A/E −/lo, CD11c −, CD115 +, CXCR4 +, CCR2 +, CX3 CR1 − ) when cultured with a Lin − c-kit + population from mouse spleen cells. The developed CD11b + cells shared a similar gene-expression profile to mononuclear phagocytes and were designated as FDMCs. Here, we describe characteristic immunological functions and the induction mechanism of FDMCs. Proliferation of anti-CD40 antibody-stimulated B cells was markedly accelerated in the presence of FDMCs. In addition, the FDMC-activated B cells efficiently acquired GC B cell-associated markers (Fas and GL-7). We observed an increase of FDMC-like cells in mice after immunization. On the other hand, FL-Y cells were found to produce CSF-1 as well as IL-34, both of which are known to induce development of macrophages and monocytes by binding to the common receptor, CSF-1R, expressed on the progenitors. However, we show that FL-Y-derived IL-34, but not CSF-1, was selectively responsible for FDMC generation using neutralizing antibodies and RNAi. We also confirmed that FDMC generation was strictly dependent on CSF-1R. To our knowledge, a CSF-1R-mediated differentiation process that is intrinsically specific for IL-34 has not been reported. Our results provide new insights into understanding the diversity of IL-34 and CSF-1 signaling pathways through CSF-1R.